Analisis Kinerja Persimpangan Tidak Bersinyal Jalan TalasalapangJalan Jipang Raya - Rianto Date Mentaruk (Universitas Kristen Indonesia Paulus, 2026)
An unsignalized intersection is a condition in which a road intersection is not equipped with traffic signal devices (such as traffic lights) to regulate the flow of vehicles. The Talasalapang – Jipang Raya road intersection is quite busy on a daily basis, with conflicting traffic flows entering and exiting the intersection. The purpose of this study is to determine the peak hour volume and the degree of saturation at the Talasalapang – Jipang Raya road intersection. The guidelines used are PKJI 2023 and the KAJI software. The results of the study show that at the Talasalapang – Jipang Raya intersection, the total peak traffic flow was 2401.4 pcu/hour, occurring on weekdays. According to the KAJI software results, the traffic flow was 3,946 pcu/hour, and the degree of saturation (Ds) in the KAJI software was 1.326. The Ds value in the KAJI software exceeded 1 because the motorcycle equivalency factor in Software KAJI is 0.5, while the EMP (equivalent motorbike passenger car unit) value for motorcycles is 0.2.